WAR, CONQUEST AND COMBAT TECHNIQUES FROM THE ANCIENT TARASCAN (Tzintzun, Revista de Estudios Históricos, 2016)
The main intention of this paper is to make a first synthesis of the data concerningthe conception of the war between the fifteenth century Purépechas. This synthesisis based on the contrast found in archaeological data, -primarily from mortuarycontexts, and ethnohistoric- contained in chronicles, dictionaries and pictures.Therefore the symbolism of weapons, the role of war and the sacrifices will beaddressed, as well as the tactical aspects and technology. From all these data it isconcluded that most of the strategies were not aimed at killing the enemy on thebattlefield but their subjugation and subsequent death on the sacrificial stone. Tosum up, the final section is an attempt to understand the war not only as a meansto feed the deities, but also as a predatory mechanism for exchanging life forcesbetween conflicting groups.
Keywords: War between Purépechas; symbolism of weapons; human sacrifices